Fresh Frozen Plasma Increases Hemorrhage in Blunt Traumatic Brain Injury and Uncontrolled Hemorrhagic Shock - Hilla Abergel; Miri Bidder; Itamar Ashkenazi; Leonid Reytman; Ricardo Alfici; Michael M. Krausz (Rambam Maimonides Medical Journal, 2023)
Background: Blunt traumatic brain injury (bTBI) and uncontrolled hemorrhagic shock (UCHS) are common causes of mortality in polytrauma. We studied the influence of fresh frozen plasma (FFP) resuscitation in a rat model with both bTBI and UCHS before achieving hemorrhage control.